HOUSE MEMBER AMENDMENT BILL NO. CS/HB 1753 AMENDMENT NO. (FOR DRAFTERS USE ONLY) (Tufts Archival Research Center, 2007)
Draft; Amendment to bill H.B. 1753 stating that there will be no difference in insurance benefits and premiums for smoking and non-smoking employees.